Relationships, Polygamy and Love in Shoneyin’s The Secret Lives of Baba Segi’s Wives: A Critical Analysis - Oliver, Bronwyn (WritingThreeSixty, 2018)
This article focuses on marital relationships in Shoneyin’s The Secret Lives of Baba Segi’s Wives. Set in a household where polygamy is practised, this article seeks to analyse Shoneyin’s exploration of the traditional and modern aspects of marriage. It looks closely at the individual wives, their reasons for entering a plural marriage, and their relationships with their husband and co-wives. Through close analysis of the text, I attempt to show how Shoneyin invites one to consider relationships and marriage as she plays off the modern conception of marriage against a traditional one. I attempt to show that the secret in the household inevitably breaks down expectations of traditional marital roles as relationships are redefined in this postcolonial setting.